2018
DOI: 10.1021/acscatal.7b03274
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reduction Promoted by Imidazole Supported on a Phosphonium-Type Ionic-Liquid-Modified Au Electrode at a Low Overpotential

Abstract: The catalytic conversion of CO 2 to useful compounds is of great importance from the viewpoint of global warming and development of alternatives to fossil fuels. Electrochemical reduction of CO 2 using aromatic Nheterocylic molecules is a promising research area. We describe a high performance electrochemical system for reducing CO 2 to formate, methanol, and CO using imidazole incorporated into a phosphonium-type ionic liquid-modified Au electrode, imidazole@IL/Au, at a low onset-potential of −0.32 V versus A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 76 publications
(145 reference statements)
2
42
0
Order By: Relevance
“…The *CHO species in this pathway is an inevitable intermediate for further reduction into methanol, ethanol, ethylene and propanol . This also explains the coexistence of formate and methanol produced on some electrodes …”
Section: Mechanistic Pathways Of Co2 Electroreduction In Aqueous Mediamentioning
confidence: 87%
“…The *CHO species in this pathway is an inevitable intermediate for further reduction into methanol, ethanol, ethylene and propanol . This also explains the coexistence of formate and methanol produced on some electrodes …”
Section: Mechanistic Pathways Of Co2 Electroreduction In Aqueous Mediamentioning
confidence: 87%
“…They observed that, under the presence of the RTIL, the overpotential for the production of CO was around 0.170 V, lower than in Au substrates in aqueous solution, obtaining a 96 % of faradic efficiency of CO. The lower CO evolution overpotential was attributed to the stabilisation of the anion radical (CO 2 − ) by complexation with the cation in the RTIL medium, i. e., RTILs act as co‐catalyst of the CO 2 RR (Figure ) . However, the co‐catalytic property of RTILs is still poorly understood, and may involve a change of the catalytic properties of the modified electrified interface apart from complex intermediate stabilisation …”
Section: Tuning the Selectivity By Engineering The Electrolyte Interfacementioning
confidence: 99%
“…The lower CO evolution overpotential was attributed to the stabilisation of the anion radical (CO 2 À ) by complexation with the cation in the RTIL medium, i. e., RTILs act as co-catalyst of the CO 2 RR (Figure 9). [153,154] However, the cocatalytic property of RTILs is still poorly understood, and may involve a change of the catalytic properties of the modified electrified interface apart from complex intermediate stabilisation. [148] Double layer effects and restructuration could also influence the CO 2 RR.…”
Section: Ionic Liquids As a Novel Approach To Increase Efficiency Andmentioning
confidence: 99%
“…In 2011, it was shown that the CO 2 ‐reduction overpotential in aqueous electrolytes could be lowered drastically by adding the IL [EMIM][BF 4 ] (1‐ethyl‐3‐methylimidazolium tetrafluoroborate) to the electrolyte, a phenomenon that was attributed to complexation of the reduced “CO 2 .− ” by the IL . Since that initial report, a number of authors have demonstrated that ILs can promote CO 2 electroreduction at low overpotentials and at different electrode materials . However, the mechanism by which ILs lower reduction overpotentials has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Since that initial report, an umber of authors have demonstrated that ILs can promote CO 2 electroreduction at low overpotentials and at different electrode materials. [13][14][15][16][17][18][19][20][21] However,t he mechanism by which ILs lower reduction overpotentials has not yet been fully elucidated. It was proposed that lowering of the pH upon hydrolysis of [BF 4 ] À increases the conversion of CO 2 to CO, whereas adsorptiono f[ EMIM] + cations onto the electrode hinders protona dsorption and competitive H 2 evolution.…”
Section: Introductionmentioning
confidence: 99%